Comparative evaluation of clonidine versus fentanyl as adjuvants for epidural anaesthesia with 0.75% ropivacaine for day care knee arthroscopy: a double-blind study - Bansal, Manoranjan Kumar; Gupta, Kumkum; Masoodi, Tahir Ahamad; Singh, V. P.; Rastogi, Bhawana; Buchh, Aqsa (International Journal of Research in Medical Sciences, 2017)
Background: Day care knee arthroscopy can be performed with general anesthesia, central neuraxial blockade and peripheral nerve blocks. The adjuvants to local anaesthetic may be used to enhance the duration of analgesia without increasing the duration of motor blockade. The present study compared the clinical efficacy of clonidine with fentanyl as adjuvants to epidural ropivacaine (0.75%) for day care knee arthroscopy. Methods: Sixty adult patients of both gender of ASA physical status I and II scheduled for day care knee arthroscopy under epidural anaesthesia, were randomized into two groups of 30 patients each to receive either 15 ml of 0.75% ropivacaine with 1 ml of clonidine 50 µg (Group RC) or with 1 ml of fentanyl 50 µg (Group RF). Groups were compared for onset and duration of sensory and motor blockade and post-anesthesia discharge score (PADS) as primary end points. Intraoperative hemodynamic changes, time taken to void, total duration of hospital stay and any adverse effects were evaluated as secondary end points. Results: The onset of complete sensory block to T10 (15.4±4.7 versus 17.5±3.8 minutes) and time to achieve complete motor block (23.7±3.3 versus 26.9±1.4 minutes) was earlier in patients of Group RC. Intraoperative hemodynamic changes were comparable. Time to achieve PADS was earlier in patients of Group RF (6.37±1.08 versus 7.11±0.49 hour) with no statistical significant difference. Total duration of hospital stays (7.81±1.31 versus 8.27± 1.18 hour) was also comparable. Conclusions: Clonidine and fentanyl, both can be used as epidural adjuvant to 0.75% ropivacaine for day care knee arthroscopy as they could enhance the duration of analgesia without affecting the hospital stay.